Analisis Kesiapan Guru dalam Implementasi Asesmen Autentik Pembelajaran Biologi pada Kurikulum Merdeka di SMA Negeri se-Kabupaten Kebumen - Ipah Budi Minarti; Rivanna Citraning Rachmawati; Winda Aulia (Journal on Education, 2022)
The teacher is someone who has an important role in implementing authentic assessments and teacher readiness is one of the success factors in implementing authentic assessments. This study aims to determine teacher readiness in implementing authentic Biology learning assessments in the independent curriculum at public high schools in Kebumen Regency, as well as knowing the supporting and inhibiting factors in its implementation. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews and documentation. The sampling technique used is simple random sampling. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study obtained an average percentage of teacher readiness in implementing authentic Biology learning assessments in the independent curriculum at public high schools in Kebumen Regency based on PAP II, namely 82% in the "very high" category. Viewed from the aspect of cognitive readiness, attitudes and emotions, and behavior or implementation obtained from the interview results, it has a percentage of 89% in the "very high" category. This is also evidenced by the percentage of completeness of authentic assessment tools used by teachers, namely 74% in the "high" category. Supporting factors include socialization and training related to authentic assessment of the independent curriculum, supporting facilities and infrastructure, collaboration between teachers, and teacher understanding and mastery of authentic assessment of the independent curriculum. Inhibiting factors include the lack of socialization and training related to authentic assessment in the independent curriculum, the large number of students with different abilities and limited time, and the lack of teachers' ability to master IT. The readiness of teachers in implementing authentic assessments of Biology learning in the independent